Living Barriers in Indian Arid Zone and them Ecological Benefits - Singh, Genda; Gupta, G. N. (Indian Forester, 2000)
The Indian arid zone, which covers mainly the States of Rajasthan, Gujarat and Haryana, was surveyed for the physical and biological benefits of the prevailing living barriers. These living barriers are generally raised to demarcate boundaries of agricultural field and to protect home yards or agricultural crops/or newly planted seedlings from dODilestic as well as wild animals. It controls runoff, facilitates the infiltration of rain water to the soil, conserve moisture and increase the production of agricultural crops. The fodder and fuel demands are also fulfilled by some of the species viz., Zizyphus sp. Prosopis julij1ora, Calligonum polygonoides, Clerodendron f1omoides, Lycium barbarum, etc. The most important benefit ofliving barriers is microclimate amelioration, particularly they moderate the hard climate. The important genera involved for the erection of living barriers are Euphorbia, Opuntia, Prosopis and Acacia. Some others are L. barbarum, C. f1omoides, B. aegiptiaca, M. emarginata, Ipomoea sp. etc. All these species have various multipurpose uses and can be generated either by direct seed sowing or by planting cuttings or nursery raised seedlings.